Reproductive patterns of Aratus pisonii (Decapoda: Grapsidae) an estuarine area of Sao Paulo Northern Coast, Brazil - de Arruda Leme, Maria Helena (1998)
The tree crab Aratus pisanii (H. MilneEdwards 1837) is a tropical sesarminae specieswidely distributed in the western Atlantic fromcentral Florida to Brazil, arid in the eastemPacific from Nioaragua to Peru (Melo 1996),being commonly found 00 the upper HUoralzone in IUangroves.